HUBUNGAN MANAJEMEN WAKTU DENGAN PRODUKTIVITAS BELAJAR MAHASISWA - Amira Tungniza; A.Rahayu Purnama Sari; Ananda dwi Putri; Rifqa Sahira; Sakila Nur Annisqa AM; Hardianto Rahman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the relationship between time management and student learning productivity. Time management is an important skill that students need to have so that academic activities can take place effectively, regularly, and directed. In college life, students are often faced with various academic demands, such as completing assignments, attending lectures, organizational activities, and preparing for exams. These conditions require students to be able to manage their time well so that all activities can be carried out in a balanced manner without reducing the quality of learning outcomes. The ability to manage time can also help students reduce the habit of procrastination, improve discipline, and create a more structured learning pattern. Student learning productivity can be seen from their ability to utilize study time optimally to achieve maximum academic results. Students who have good time management tend to be better able to determine activity priorities, organize study schedules, and use time efficiently. Conversely, students who are less able to manage their time often experience delays in completing assignments, lack focus in studying, and experience decreased academic motivation. Therefore, time management is one of the important factors that can influence student learning success. This study uses a quantitative method with a correlational approach. Data were obtained through questionnaires distributed to students as research respondents and then analyzed using the Spearman correlation test with the help of the JASP application. The results showed a positive and significant relationship between time management and student learning productivity. This is evidenced by a correlation coefficient of 0.784 and a significance value of p < 0.05. This value indicates a strong relationship between the two variables. This means that the better a student's time management skills, the higher their learning productivity.